Pengaruh kompensasi kerja, disiplin kerja, dan sarana prasarana terhadap kinerja guru di Yayasan Persatuan Perguruan Tamansiswa cabang Kebumen - Suwarko Suwarko; Samidjo Samidjo (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2016)
This study aimed to determine: (1) the Influence of compensation, discipline and infrastructure work on the performance of teacher of Tamansiawa Foundation. Kebumen, (2) the Influence of compensation on the performance of teachers working at Tamansiawa Foundation Kebumen, (3) the influence of discipline on the performance of Teacher of Tamansiawa Foundation Kebumen, (4) the influence of Infrastructure on the performance of Teacher of Tamansiawa Foundation Kebumen. The population in this study was all teachers at Tamansiawa Foundation. Kebumen. Determination of the number of the subject of the sample in this study using a nomogram Harry King and the number of sample in this study was 148 teachers. The sampling method used was proportionate random sampling. Data obtained by distributing questionnaires to 148 respondents and then the data were analyzed and by using the software Statistical Package for Social Science (SPSS) version 16 with multiple regression and partial analysis. The research results, conclude that: (1) There is a positive and significant Influence of compensation, work discipline, and infrastructure simultaneously on teacher performance, meaning an increase in compensation, discipline, and infrastructure influence the performance of teachers. (2) There is a positive and significant influence partially compensation work on teacher performance, meaning that the higher compensation that is given will make the higher the performance. (3) There is a positive and significant influence of discipline partially on teacher performance, meaning that the higher the level of work discipline that is applied to make the higher the performance of the teacher. (4) There is a positive and significant influence of infrastructure partially on teacher performance, this indicates a good infrastructure will create a comfortable and healthy so it can work better, as well as infrastructure that supports the complete facility will be able to improve the performance of the teacher.